Determination of the Supply and Rational Manufacturing Volume by Application of Marginal Analysis - Zabielavičienė, Irena; Arimavičiūtė, Malvina (Ekonomika, 2001)
The paper deals with marginal theory conclusions with the view of their application in the investigation of Lithuanian State economy. A lot of methodical problems arise in making out the supply curve of marginal costs principals application. It is imperative to make parameters of functions, approximating the average fixed, variable, total and marginal costs. The approximation of average variable and average total costs must be very precise in minimal expressions’ intervals. Inexact variable costs approximation distorts marginal costs. For these reasons actually it is not possible to approximate average, total and marginal costs by any function. We have to apply the method of functions segment joining. Defining the production supply of Republic it is necessary to sum up the supply curves of enterprises. Therefore it’s important to know not only the parameters of marginal costs functions, but intervals as well, in which it is possible on the crossing point of marginal costs curve with the average variable costs curve (for the short-term supply) and with average total costs (for the long-run supply) curves. The above mentioned theory does not present the ways how to define the maximum supply points of enterprises. Every enterprise extends the production by using extensive labor force only for the time the rational supply of labor force with capital assets is reached. The rational labor supply with capital assets is not a stable measure. It varies according to technical advancement and other factors. Thus, it is necessary to analyze the labor in retrospective and perspective periods. This might be carried out by dynamical analysis. The prediction is made for concrete perspective period year the optimal amount labor supply with capital assets and the total output. According to this, the maximum of production supply curves points are achieved. Having the marginal costs function’s parameters of enterprises and intervals in which aforesaid functions might be identified with supply curves, minimal and maximal expressions, it becomes possible to sum up these curves. In such a way we may set up a supply curve for a concrete branch of economy. Marginal analysis helps to estimate the rational production volume, that ensures max profit (if enterprise operates profitably) or min losses (if it operates unprofitably). However, the use of this method in practice is complicated. That is why the application of theoretical propositions of marginal analysis should be modified for the enterprises that are expanding their production extensively. The paper deals with problems of marginal analysis modification.